Carnival - Helldorfer, Mary-Claire, 1954-; Yaccarino, Dan (New York : Viking, 1996)
A carnival offers all the fun and excitement of flying balloons, shooting basketballs, riding ponies, and walking through a haunted house.
Horn Book Starred
School Library Journal
Wilson's Children
1.5
K-3
K-3
Keywords: Carnivals -- Fiction; Stories in rhyme; Carnivals -- Fiction; Stories in rhyme